2021
DOI: 10.1136/bmjopen-2020-041599
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and impact of international medical volunteering: a multi-country mixed methods study

Abstract: ObjectiveTo assess the experience and impact of medical volunteers who facilitated training workshops for healthcare providers in maternal and newborn emergency care in 13 countries.SettingsBangladesh, Ghana, India, Kenya, Malawi, Namibia, Nigeria, Pakistan, Sierra Leone, South Africa, Tanzania, UK and Zimbabwe.ParticipantsMedical volunteers from the UK (n=162) and from low-income and middle-income countries (LMIC) (n=138).Outcome measuresExpectations, experience, views, personal and professional impact of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Our interviews revealed that contributions of this nature by the volunteers triggered a spirit of initiative and empowerment throughout all the communities, again supporting the findings of other research (Devereux 2008;Kambutu and Nganga 2008;Wu 2011;McCauley et al 2021). This shows that communities can find solutions to their own problems when they are empowered to do so.…”
Section: Impacts Of Volunteeringsupporting
confidence: 87%
See 1 more Smart Citation
“…Our interviews revealed that contributions of this nature by the volunteers triggered a spirit of initiative and empowerment throughout all the communities, again supporting the findings of other research (Devereux 2008;Kambutu and Nganga 2008;Wu 2011;McCauley et al 2021). This shows that communities can find solutions to their own problems when they are empowered to do so.…”
Section: Impacts Of Volunteeringsupporting
confidence: 87%
“…As a result, the activities and roles of volunteers are gradually being formalised, institutionalised and recognised in many countries around the world (Brown and Green 2015;United Nations Economic and Social Council 2001). The underlying assumption is that volunteering and 'doing good' will at least lead to a positive transformation in the local or host community (Bussell and Forbes 2002;Haddad 2007;Unstead-Joss 2008;Butcher and Smith 2010;McCauley et al 2021).…”
Section: Introductionthe Emerging Phenomenon Of Volunteerismmentioning
confidence: 99%
“…There are numerous reports on the Urolink website of the benefits that trainees have accrued from working in a different healthcare environment, seeing different pathologies and working within an environment with significant resource constraints [31,32]. However, the risks of having HIC trainees in an LMIC centre are that they may be incapable of working without close supervision in difficult operating environments, they may engender additional work for the host unit and their presence can result in a loss of training opportunities for local trainees [29]. The advantages from trainee STSTs are, however, massive by comparison, helping build lifelong links between trainees from LICs and HICs [33], as well as being able to provide additional help with training, especially information about evidence‐based practice [34].…”
Section: The Value Of Longer Visits From Established To Trainee Surge...mentioning
confidence: 99%
“…The ability of fully trained professionals to spend long periods of time assisting abroad is limited by their need to establish their practice in their country of origin, by finance, and by the pressures of family life. The value to the individual surgeons and the NHS in visiting and supporting units abroad is, however, well established [27][28][29]. Although a number of consultants have spent extended periods at KCMC during their careers, the ideal time to visit would appear to be in the peri-retirement era, when the professional and domestic needs of the individual allow more flexibility to travel.…”
Section: The Value Of Longer Visits From Established To Trainee Surge...mentioning
confidence: 99%
“…It is vitally important that anyone helping in the educative process is giving something to the liaison with the host department so that they develop a durable relationship with demonstrable, sustainable, benefit. Ethical considerations should be paramount when considering a link with a urologist in a resource‐poor setting [43] to ensure that no one in the host institution is disadvantaged by the presence of surgeons, trainees or nurses from the helper HIC [44–46].…”
Section: Appropriatenessmentioning
confidence: 99%